2022
DOI: 10.1200/jco.2022.40.4_suppl.581
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose-escalation study of eryaspase in combination with modified FOLFIRINOX in locally advanced and metastatic pancreatic ductal adenocarcinoma: Interim update.

Abstract: 581 Background: The prognosis for advanced metastatic pancreatic adenocarcinoma remains dismal with median survival of 12-15 months in most recent trials, highlighting the urgent need for novel therapeutic agents. mFOLFIRINOX remains the standard of care for the first line treatment of advanced disease, with historical objective response rate (ORR) of ̃31%. Eryaspase, L-asparaginase (ASPNase) encapsulated in red blood cells (RBCs), is an investigational product under development. Following infusion, asparagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a randomized, open-label phase III trial (Trybeca-1), the combination of eryaspase with GnP or irinotecan/5-FU failed to meet the primary endpoint of patient OS, however, in the irinotecan/5-FU subgroup, eryaspase group showed good tolerability and survival benefit and warrants additional study (NCT03665441) 39 . Another phase I trial used eryaspase in combination with mFOLFIRINOX for the first-line treatment of locally advanced or mPDAC (NCT04292743), with results to be further observed 40 . In addition, Pathria et al 41 found that inhibition of asparagine activated receptor tyrosine kinase-MAPK signaling and enhanced translation of transcription factor 4 (ATF4) mRNA in pancreatic cancer cells.…”
Section: Targeting Metabolic Vulnerabilitiesmentioning
confidence: 99%
“…In a randomized, open-label phase III trial (Trybeca-1), the combination of eryaspase with GnP or irinotecan/5-FU failed to meet the primary endpoint of patient OS, however, in the irinotecan/5-FU subgroup, eryaspase group showed good tolerability and survival benefit and warrants additional study (NCT03665441) 39 . Another phase I trial used eryaspase in combination with mFOLFIRINOX for the first-line treatment of locally advanced or mPDAC (NCT04292743), with results to be further observed 40 . In addition, Pathria et al 41 found that inhibition of asparagine activated receptor tyrosine kinase-MAPK signaling and enhanced translation of transcription factor 4 (ATF4) mRNA in pancreatic cancer cells.…”
Section: Targeting Metabolic Vulnerabilitiesmentioning
confidence: 99%
“…There is currently an ongoing phase I trial of eryaspase plus mFOLFIRINOX (fluorouracil, oxaliplatin, irinotecan) in the front-line setting for PDAC. Interim analysis was encouraging, with 50% PR (5 of 10 patients) and 100% DCR [ 156 ]. There were no dose-limiting toxicities.…”
Section: Metabolic Pathwaysmentioning
confidence: 99%